MANAGEMENT OF PUBLIC ROADSIDE PARKING BY THE TRANSPORTATION DEPARTMENT OF COMMUNICATION AND INFORMATICS PEKANBARU IN 2013 - muhammad Ridwan; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Pekanbaru City as Cipil Town of Riau Province has a high traffic degree. That’s why, Pekanbaru needs enough parking area with a good management. Indonesian Constution allowed activities on public roadside parking based on traffic sign. But in fact, the implementation doesn’t works effectively because so many illegal parking area with illegal retributions. It’s make a cause to diminution of native territorial income that never rich the goal. One of the unsolved problems until today such as on public roadside parking of Tuanku Tambusai street and throughout the front of Cik Puan Market that makes traffic jam.This research is supposed see the management constitution implementations of public roadside parking from Dishubkominfo Pekanbaru city. Management theory is a base to this qualitative research. Based on analysis from the writer, the ineffectively management implementations is because of Parking UPTD of Dishubkominfo doesn’t have a written management and programs planning. Parking UPTD of Dishubkominfo can not acting explicitly because still have a good parking area to solve the problems.Key words : Management, Public Roadside Parking, Pekanbaru city.